The Influence of Transformational Leadership and Organizational Culture on Innovative Behavior of Civil Servant Teachers at SMA Negeri 1 Sungai Raya Kubu Raya West Kalimantan - Surya Ningsih; Devi Yasmin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Human resources are organizational elements that determine the continuity of activities and the achievement of objectives, including in public organizations within the state senior secondary education sector. At SMA Negeri 1 Sungai Raya, Kubu Raya Regency, dynamics are still found in the implementation of organizational culture and work behavior of Civil Servant (ASN) teachers, such as time discipline that is not yet fully consistent and differences in adaptability to technology-based learning methods. These conditions occur alongside the implementation of ASN work culture values BerAKHLAK and the continuously developing demands for instructional innovation. This study examines the influence of transformational leadership and organizational culture on the innovative behavior of Civil Servant teachers, both partially and simultaneously. This study aims to analyze the influence of transformational leadership and organizational culture on the innovative behavior of Civil Servant teachers at SMA Negeri 1 Sungai Raya, Kubu Raya Regency, West Kalimantan. This study uses a quantitative approach with an associative design. The research respondents consist of 52 ASN teachers, all of whom were used as samples through total sampling techniques. Data were collected through interviews and questionnaires using a Likert scale and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation and determination analysis, and simultaneous and partial hypothesis testing. The results show that transformational leadership and organizational culture have a positive and significant influence on teachers’ innovative behavior, both partially and simultaneously. These findings indicate that inspirational leadership and an organizational culture that supports openness, cooperation, and adaptability play an important role in encouraging innovative behavior among teachers in carrying out their professional duties in public school environments.